Oncolytic Adenovirus—A Nova for Gene-Targeted Oncolytic Viral Therapy in HCC - Abudoureyimu, Mubalake; Lai, Yongting; Tian, Chuan; Wang, Ting; Wang, Rui; Chu, Xiaoyuan (Frontiers in Oncology, 2019)
Hepatocellular carcinoma (HCC) is one of the most frequent cancers worldwide, particularly in China. Despite the development of HCC treatment strategies, the survival rate remains unpleasant. Gene-targeted oncolytic viral therapy (GTOVT) is an emerging treatment modality—a kind of cancer-targeted therapy—which creates viral vectors armed with anti-cancer genes. The adenovirus is a promising agent for GAOVT due to its many advantages. In spite of the oncolytic adenovirus itself, the host immune response is the determining factor for the anti-cancer efficacy. In this review, we have summarized recent developments in oncolytic adenovirus engineering and the development of novel therapeutic genes utilized in HCC treatment. Furthermore, the diversified roles the immune response plays in oncolytic adenovirus therapy and recent attempts to modulate immune responses to enhance the anti-cancer efficacy of oncolytic adenovirus have been discussed.